Determinants of rural households' livelihood diversification strategies: In the case of north Wollo zone, Amhara National Regional State, Ethiopia - Andualem Kassegn; Umer Abdinasir (Cogent Economics & Finance, 2023)
Diversifying rural livelihoods plays a significant role for rain feed-dependent economy of the rural households like in Ethiopia. Hence the objective of the study was to investigate the determinants of rural households' livelihood diversification strategies choice in north wollo zone of Ethiopia. A multi-stage stratified random sampling technique was used to select 384 rural household heads as a sample in study areas. Primary data was collected from sample rural household heads using an interview schedule. Multivariate Probit Model was employed to identify the factors influencing the rural household heads' decision to choose livelihood strategies. The model result showed that agriculture livelihood strategy was positively and significantly associated with male headed household, land holding, cooperative membership, and participation in rural productive safety net program; while it is negatively and significantly affected by distance to market. Non-farm livelihood strategy was positively and significantly affected by dependency ratio, education level, total income, and remittance; while it is negatively and significantly affected by the sex of household head and participation in rural productive safety net program. Off-farm livelihood strategy was positively and significantly influenced by sex of household head; while it is negatively and significantly affected by the land holding, total livestock unit, cooperative membership, credit use, participation in rural productive safety net program. Therefore, the study recommends that local government should attempt to promote the above significant determinants of rural households' livelihood diversification strategies choice to build more profitable and sustainable livelihood strategies.
Keywords: 330; Agriculture; Livelihood strategies choice; MVP; Non-farm; Off-farm